Avaliação do tratamento da periodontite na expressão de marcadores sistêmicos da aterosclerose: ensaio clínico - Toregeani, Jeferson Freitas (2013)
Atherosclerotic disease, one of the leading causes of morbidity and mortality in the world, expresses inflammatory markers that can be evaluated in the laboratory or by Doppler ultrasound, that can detect common carotid artery intima-media thickening (IMT), which is a precursor morphological change of atherosclerotic disease. The atherosclerotic disease risk factors most relevant are diabetes, hypertension, hypercholesterolemia and smoking. Periodontal disease, which has a high prevalence worldwide, has been increasingly correlated to atherosclerotic disease, where the bacterial activity and the inflammatory process in the periodontal tissues seem to aggravate atherosclerosis. The objectives of this research were to evaluate the treatment of periodontal disease and the influence of this treatment on the variation of thickness of the common carotid artery miointimal complex and the variations of laboratory parameters. Forty-four volunteers patients were divided into 2 groups, healthy patients 23 (GI) and 21 patients with moderate to severe periodontitis (GII). All patients underwent clinical and nutritional assessment. Also periodontal clinical parameters were evaluated: plaque index (PI), gingival index (IS), probing depth (PS), clinical attachment level (NI) and bleeding on probing (SS). The patients were submitted to assess carotid intima-media thickness and to laboratory evaluation by collecting of counting blood cells, creatinine, total cholesterol and fractions, triglycerides, fibrinogen, C-reactive protein, homocysteine, erythrocyte sedimentation rate, fasting blood glucose and glycated hemoglobin. All patients received the basic periodontal treatment and only group II were submitted to mechanical control with scaling and root planning and coronary sinus polishing. Data were obtained in the pre-treatment, with 6 months and after 12 months from the beginning of the study. The results showed a significant improvement in periodontal clinical parameters in both groups (p < 0,05), more evident between the first and second evaluations and greater in GII (p < 0,05). There were a decrease of triglycerides and low-density lipoprotein in GI and increase in their levels in GII (p < 0,05), increased Fibrinogen along the GI study (p < 0,05) and decrease in glycated hemoglobin concentration in both groups. The average counts of erythrocytes, hematocrit, hemoglobin and platelets were lower in the last reviews. The variation of the amount of platelets was significantly higher in the first phase of the GI (p < 0,05). There was a decrease IMT in 2 groups in the first phase, and fall of systolic and diastolic velocity, pulsatility and resistivity index in the second phase of both groups (p < 0,05). Thus, based on the results, treatments imposed were effective in improving the periodontal clinical parameters of patients with periodontitis and toothbrushing associated with dental floss and the motivation of oral hygiene was also effective in the improvement of clinical periodontal parameters even in relatively healthy patients. The improvement of periodontal parameters promoted significant effect on reduction of IMT in both groups, in the initial period of 6 months. At the end of the study (360 days), there was no significant effect of changes in periodontal clinical parameters in IMT variations in both groups I and II